Engulfment and cell motility protein 1 fosters reprogramming of tumor-associated macrophages in colorectal cancer - Wen, Bo; Li, Sheng; Ruan, Lei; Yang, Yanping; Chen, Zilin; Zhang, Bin; Yang, Xin; Jie, Haiqing; Li, Shujuan; Zeng, Ziwei; Liu, Sisi (Cancer science, 2023)
Functional reprogramming of tumor-associated macrophages (TAMs) is crucial to their potent tumor-supportive capacity. However, the molecular mechanism behind the reprogramming process remains poorly understood. Here, we identify engulfment and cell motility protein 1 (ELMO1) as a crucial player for TAM reprogramming in colorectal cancer (CRC). The expression of ELMO1 in stromal but not epithelial tumor cells was positively associated with advanced clinical stage and poor disease-free survival in CRC. An increase in ELMO1 expression was specifically found in TAMs, but not in other multiple nonmalignant stromal cells. Gain- and loss-of-function assays indicated ELMO1 reprogrammed macrophages to a TAM-like phenotype through Rac1 activation. In turn, ELMO1-reprogrammed macrophages were shown to not only facilitate the malignant behaviors of CRC cells but exhibited potent phagocytosis of tumor cells. Taken together, our work underscores the importance of ELMO1 in determining functional reprogramming of TAMs and could provide new insights on potential therapeutic strategies against CRC.